The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1109/tmm.2015.2430819
|View full text |Cite
|
Sign up to set email alerts
|

Relational User Attribute Inference in Social Media

Abstract: Nowadays, more and more people are engaged in social media to generate multimedia information, i.e., creating text and photo profiles and posting multimedia messages. Such multimodal social networking activities reveal multiple user attributes such as age, gender, and personal interest. Inferring user attributes is important for user profiling, retrieval, and personalization. Existing work is devoted to inferring user attributes independently and ignores the dependency relations between attributes. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 29 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…They proposed two different security schemes to provide confidentiality and business data collection via distributed storage. Although various authors [35] have proposed several secure decision-making and inference schemes, very few of them have focused on data alteration, message transmission, and sharing of records through legitimate devices. Further, researchers have proposed some lightweight cryptographic algorithms to further improve the security in IoV systems.…”
Section: Outlinementioning
confidence: 99%
“…They proposed two different security schemes to provide confidentiality and business data collection via distributed storage. Although various authors [35] have proposed several secure decision-making and inference schemes, very few of them have focused on data alteration, message transmission, and sharing of records through legitimate devices. Further, researchers have proposed some lightweight cryptographic algorithms to further improve the security in IoV systems.…”
Section: Outlinementioning
confidence: 99%
“…This includes work on gender (Burger, 2011), political affiliation (Conover, 2011;Pennacchiotti, 2011), location (Cheng, 2010) and ethnicity (Mislove, 2011;Chang, 2010;Pennacchiotti, 2011). Also of note is the work of Fang (2015) who focus on modelling the correlations between various demographic attributes.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, an intruder may launch a data falsification attack, also known as a false data injection attack, to perform various malicious activities (active/passive threats) inside the network [17]- [19]. Lidkea et al [20] have identified another critical threat specific to ITSs using social media, where attackers gain access to sensitive information through e-mails and other social media interactions [21]- [24] by stealing the database or records of a device or a server.…”
Section: Introductionmentioning
confidence: 99%